Optimum Design of GA-BF Algorithm Based PID Controller for the Solar System - S. Mallika; R. Saravanakumarf (International Journal of Advances in Applied Sciences, 2017)
This paper presents a new approach based on the genetic algorithm (GA) and Bacterial Foraging (BF) is used to perform a constrained tuning technique for the PID parameters to optimize the power output of solar panel. A small-signal model is used to design the controller parameters of the conventional PID controller. The dynamics of the converter is non linear, therefore, it is hard to derive desirable performance. So hybrid algorithm is used to optimize the control parameters of boost converter. In order to obtain the fitness of an individual, Simulink model of the boost converter is designed and the hybrid algorithm is programmed to design the optimal control parameters. It was found that the proposed optimal PID controller parameters adjustment by the GA-BF algorithm is superior to the conventional method. The Matlab/Simulink was used to verify the effectiveness of proposed control method.